An electrochemical carbon dioxide reduction device and methods of making and using

CN122522274BActive Publication Date: 2026-10-09HUNAN QIWEI HYDROGEN ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611016657.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09
Estimated Expiration
2046-07-09

AI Technical Summary

Technical Problem

[0004]1.选择性与活性矛盾:PEM 电解槽的酸性环境有利于质子传输,但会加速析氢副反应,降低CO2RR制CO的选择性;

Benefits of technology

[0058] This invention uses a 175μm modified N117 proton exchange membrane as its core, designs a membrane electrode assembly, and applies the assembly to a PEM electrolyzer CO2RR CO production device. Through precise adaptation of the membrane, electrodes, and process, the contradiction between thick-film proton conduction and thin-film stability is resolved. Its advantages include:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122522274B_ABST
    Figure CN122522274B_ABST
Patent Text Reader

Abstract

The application discloses a kind of electrochemical reduction carbon dioxide device and preparation and use method;Belong to electrochemical energy conversion technical field.The device includes membrane electrode assembly, the membrane electrode assembly is by cathode catalyst layer, anode catalyst layer, N117 proton exchange membrane is composed, wherein cathode catalyst layer, anode catalyst layer are located at the two sides of proton exchange membrane respectively, and adhere on proton exchange membrane;The material of cathode catalyst layer is OD-Ag / CNT catalyst, and the material used for anode catalyst layer is IrO2 catalyst.Its preparation method includes first modifying proton exchange membrane, then setting for position coating catalyst, finally hot-pressing membrane electrode assembly is obtained.The membrane electrode assembly is finally assembled into PEM electrolytic cell and constitutes CO2RR preparation CO device.The application has reasonable structure design, simple and controllable preparation process, and the obtained product has excellent performance, and is convenient for industrialization application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention discloses an electrochemical carbon dioxide reduction device and its preparation and use method; specifically, it relates to a device and its preparation and use method for carbon monoxide (CO) produced by carbon dioxide electroreduction (CO2RR) based on a proton exchange membrane (PEM) electrolyzer, belonging to the field of electrochemical energy conversion technology. Background Technology

[0002] Currently, carbon dioxide capture and conversion technology has become a research hotspot in the energy and chemical industry. Electrochemical reduction of carbon dioxide (CO2RR) can convert CO2 into high-value-added chemicals such as carbon monoxide (CO), formic acid, and ethylene under mild conditions. Among them, CO, as an important component of syngas (CO+H2), is a key raw material for the preparation of chemical products such as methanol and Fischer-Tropsch synthetic oil.

[0003] Proton exchange membrane (PEM) electrolyzers have been commercially applied in water electrolysis for hydrogen production due to their advantages such as high current density (up to 500-1000 mA / cm²), high energy efficiency (≥70%), high product purity, and fast system response. However, their application in CO2RR for CO production still faces three major challenges:

[0004] 1. The contradiction between selectivity and activity: The acidic environment of the PEM electrolyzer is conducive to proton transport, but it will accelerate the hydrogen evolution side reaction and reduce the selectivity of CO2RR to CO.

[0005] 2. Catalyst stability issues: Under acidic conditions, most metal catalysts are prone to dissolution and loss. Although Ag catalysts have high selectivity for CO, they are prone to agglomeration and oxidation under high current densities.

[0006] 3. Mass transfer and proton conduction synergy and membrane stability issues: CO2 gas needs to diffuse efficiently to the catalytic active site, while protons need to be transported rapidly through the membrane. Traditional thin proton exchange membranes are prone to CO2 transmembrane diffusion and oxidative degradation, while thick membranes are prone to low proton conduction efficiency.

[0007] In the prior art, patent application CN116293761A discloses an electrochemical carbon dioxide reduction device, which includes a silver-based cathode and a platinum-based anode, and a Nafion 117 proton exchange membrane. The device is powered by a regenerative battery stack and can perform secondary treatment of carbon dioxide. In this further technology, the electrochemical carbon dioxide reduction device achieves a Faraday efficiency of 72% in reducing carbon dioxide to carbon monoxide at the optimal operating voltage of 6V. Summary of the Invention

[0008] To reduce the voltage required for the electrochemical reduction of carbon dioxide and improve the Faraday efficiency, this invention, for the first time, employs an oxide-derived silver (OD-Ag) / carbon nanotube (CNT) catalyst as the cathode and an IrO2 catalyst as the anode, along with a Nafion 117 proton exchange membrane, to develop a high-quality electrochemical carbon dioxide reduction device. Simultaneously, the method for using this device has also been developed.

[0009] The present invention discloses an electrochemical carbon dioxide reduction device; the device includes a membrane electrode assembly (abbreviated as MEA), which is composed of a cathode catalyst layer 5-1, an anode catalyst layer 5-2, and an N117 proton exchange membrane 6, wherein the cathode catalyst layer 5-1 and the anode catalyst layer 5-2 are located on both sides of the N117 proton exchange membrane 6 and are attached to the N117 proton exchange membrane 6.

[0010] The cathode catalyst layer 5-1 is made of oxide-derived silver (OD-Ag) / carbon nanotube (CNT) catalyst, and the anode catalyst layer 5-2 is made of IrO2 catalyst.

[0011] The oxide-derived silver (OD-Ag) / CNT catalyst used was prepared by the following method:

[0012] Prepare AgNO3 and carbon nanotubes (CNTs) by mass ratio of AgNO3:CNT = 1:0.4~0.6. Then dissolve the prepared AgNO3 in deionized water, add the prepared carbon nanotubes to it, and disperse evenly by ultrasonication. Adjust the pH of the solution system to 9.8~10.2, and stir the reaction for at least 1 hour to obtain the Ag2O / CNT precursor.

[0013] An Ag₂O / CNT precursor was coated onto a carbonaceous current collector as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. The catalyst was reduced at a constant potential of -0.18 to -0.22 V, preferably -0.2 V, for at least 30 min in a 0.4–0.6 mol / L H₂SO₄ solution to obtain an OD-Ag / CNT catalyst with a current collector; the voltage is relative to the RHE (Reduced Heating Equivalent).

[0014] The catalyst was then stripped from the carbonaceous current collector, washed with deionized water until neutral, and finally dried under vacuum to obtain the OD-Ag / CNT catalyst.

[0015] Preferably, the thickness of the N117 proton exchange membrane is 175 μm.

[0016] To further improve the performance of the equipment, the N117 proton exchange membrane is a modified N117 proton exchange membrane. The modification process is as follows: First, a 175 μm thick N117 proton exchange membrane is placed in a solution of 5% H2O2 and 0.5 mol / L H2SO4, heated to 95-105°C, and held at this temperature for at least 30 minutes, preferably 45-75 minutes, and more preferably 60 minutes, to obtain a pre-modified N117 proton exchange membrane. The pre-modified N117 proton exchange membrane is then placed in deionized water and heated to 95-105°C, held at this temperature for at least 30 minutes, preferably 45-75 minutes, and more preferably 60 minutes, to obtain a modified N117 proton exchange membrane. After cooling to room temperature, the membrane is drained, maintaining its wetted state. This modification improves the proton conductivity of the membrane.

[0017] Preferably, the oxide-derived silver (OD-Ag) / CNT catalyst is prepared by electrochemical reduction of Ag₂O precursor, with OD-Ag particle size of 10–100 nm and surface defect density of 1.2–1.6 × 10⁻⁶. 18 CNTs, with a density of 1 per m², provide high specific surface area and conductivity as a carrier.

[0018] The present invention discloses a method for preparing an electrochemical carbon dioxide reduction device, comprising the following steps:

[0019] Step 1: First, place a 175μm thick N117 proton exchange membrane in a solution of 5% H2O2 and 0.5mol / L H2SO4, heat it to 95~105℃, and keep it at that temperature for at least 30min, preferably 45~75min, and more preferably 60min to obtain a pre-modified N117 proton exchange membrane. Then, place the pre-modified N117 proton exchange membrane in deionized water, heat it to 95~105℃, and keep it at that temperature for at least 30min, preferably 45~75min, and more preferably 60min to obtain a modified N117 proton exchange membrane.

[0020] Step 2: Prepare 0.2-0.3 g of OD-Ag / CNT catalyst by mixing 90-150 μL of Nafion solution and 50-75 mL of mixed solvent. Mix the OD-Ag / CNT catalyst, Nafion solution, and mixed solvent thoroughly to obtain cathode catalyst ink. Then, spray the cathode catalyst ink onto one side of the modified N117 proton exchange membrane to obtain a modified N117 proton exchange membrane with cathode catalyst. The spraying temperature is 70-90℃, and the loading of OD-Ag / CNT catalyst on the modified N117 proton exchange membrane is 0.5-2.0 mg / cm³. 2 The preferred concentration is 0.8~1.0 mg / cm³. 2A further preferred value is 0.9 mg / cm³. 2 ;

[0021] Step 3: Mix the IrO2 catalyst, Nafion solution, and mixed solvent evenly according to the ratio of 0.15~0.3g IrO2 catalyst, 60~100μL Nafion solution, and 10~20mL mixed solvent to obtain the anolyte catalyst ink; spray the anolyte catalyst ink onto the other side of the modified N117 proton exchange membrane; thus obtaining a modified N117 proton exchange membrane with a cathode catalyst on one side and an anolyte catalyst on the other side.

[0022] The spraying temperature was 70~90℃, and the loading of the anolyte catalyst on the modified N117 proton exchange membrane, which had a cathode catalyst on one side and an anolyte catalyst on the other side, was 0.8~1.2 mg / cm³. 2 Preferred concentration: 1.0 mg / cm³ 2 ;

[0023] Step 4: Under conditions of 120~160℃, preferably 140℃, and 3~8MPa, preferably 7.0MPa, the modified N117 proton exchange membrane with a cathode catalyst on one side and an anode catalyst on the other side is hot-pressed to obtain MEA, with a contact resistance between the membrane and the catalyst layer ≤5 mΩ・cm².

[0024] Preferably, the oxide-derived silver (OD-Ag) / CNT catalyst used in step two of this invention is prepared by the following method:

[0025] Prepare AgNO3 and CNT by mass ratio of AgNO3:CNT = 1:0.4~0.6, then dissolve the prepared AgNO3 in deionized water, add the prepared carbon nanotubes to it, and after ultrasonic dispersion, adjust the pH of the solution system to 9.8~10.2, stir the reaction for at least 1 hour to obtain Ag2O / CNT precursor;

[0026] An Ag₂O / CNT precursor was coated onto a carbonaceous current collector as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. The reaction was carried out in a 0.4–0.6 mol / L H₂SO₄ solution at a constant potential of -0.18–-0.22 V for at least 30 min to obtain an OD-Ag / CNT catalyst with a current collector; the voltage is relative to the RHE.

[0027] The catalyst was then stripped from the carbonaceous current collector, washed with deionized water until neutral, and finally dried under vacuum to obtain the OD-Ag / CNT catalyst.

[0028] As a further preferred embodiment, the oxide-derived silver (OD-Ag) / CNT catalyst used in step two of this invention is prepared by the following method:

[0029] Dissolve 1g AgNO3 in 50mL deionized water according to the ratio, add 0.5g CNT and sonicate for 30min, add 2mol / L NaOH solution to adjust pH to 10, stir and react for 2h to obtain Ag2O / CNT precursor;

[0030] The precursor was coated onto a carbonaceous current collector as the working electrode, a platinum sheet was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The catalyst was reduced in 0.5 mol / L H2SO4 solution at a constant potential of -0.2 V (vs. RHE) for 60 min to obtain the OD-Ag / CNT catalyst with the current collector.

[0031] In industrial applications, the catalyst is stripped from the carbonaceous current collector, washed with deionized water until neutral, and then vacuum dried at 60°C for 12 hours for later use.

[0032] The OD-Ag catalyst prepared by this method has abundant active sites, which can significantly improve CO2 adsorption capacity and CO selectivity, reduce the efficiency of hydrogen evolution side reaction to below 10%, and when used in combination with modified N117 proton exchange membrane, it can maintain a low overpotential at a current density of 1000 mA / cm², ensuring the energy efficiency of the device.

[0033] Preferably, in step two of this invention, 0.24 g of OD-Ag / CNT catalyst, 105 μL of Nafion solution (20 wt%), and 67.8 mL of mixed solvent (ethanol:water = 1.76:1) are mixed in proportion and ultrasonically dispersed for 60 min. Then, the catalyst ink is coated onto the modified N117 proton exchange membrane using an ultrasonic spraying method at a temperature of 80 °C. The loading of OD-Ag / CNT catalyst on the modified N117 proton exchange membrane is 0.9 mg / cm³. 2 .

[0034] In step three of this invention, 0.21g of IrO2 catalyst, 80 μL of Nafion solution and 10mL of mixed solvent are mixed in proportion and ultrasonically dispersed for 60min to obtain anode catalyst ink; the mixed solvent is composed of ethanol and water in a mass ratio of ethanol:water = 1.76:1.

[0035] The anolyte catalyst ink was sprayed onto the other side of the modified N117 proton exchange membrane, resulting in a modified N117 proton exchange membrane with a cathode catalyst on one side and an anolyte catalyst on the other side. The spraying temperature was 80℃, and the loading of the anolyte catalyst on the modified N117 proton exchange membrane with a cathode catalyst on one side and an anolyte catalyst on the other side was 1.0 mg / cm³. 2 .

[0036] The solid content in the cathode catalyst ink is 0.35~0.45wt%, preferably 0.38~0.42wt%, and more preferably 0.4wt%.

[0037] The solid content in the anode catalyst ink is 0.30~0.35wt%, preferably 0.35wt%.

[0038] In this invention, the loading of the anode catalyst is slightly greater than that of the cathode catalyst. Through proper adaptation, the overall efficiency of the equipment reaches a high level.

[0039] The present invention relates to the application of an electrochemical carbon dioxide reduction device, which includes assembling it into a PEM electrolyzer to form a CO2RR CO production device.

[0040] The PEM electrolyzer includes two end plates 1, two bipolar plates with flow channels 2, two sealing rings 3, a cathode gas diffusion layer 4-1, an anode gas diffusion layer 4-2, a cathode catalyst layer 5-1, an anode catalyst layer 5-2, and an N117 proton exchange membrane 6. The cathode catalyst layer 5-1 and the anode catalyst layer 5-2 are located on opposite sides of the modified N117 proton exchange membrane 6 and are attached to it. The cathode gas diffusion layer 4-1 is in contact with the cathode catalyst layer 5-1, and the anode gas diffusion layer 4-2 is in contact with the anode catalyst layer 5-2. One of the two sealing rings 3 is located on one side of the cathode gas diffusion layer 4-1, and the other sealing ring 3 is located on one side of the anode gas diffusion layer 4-2.

[0041] Two bipolar plates 2 with flow channels are respectively arranged on one side of two sealing rings 3, and two end plates 1 are respectively arranged on one side of two bipolar plates 2 with flow channels;

[0042] With the modified N117 proton exchange membrane 6 as the axis of symmetry, the two end plates 1, the two bipolar plates 2 with flow channels, and the two sealing rings 3 are arranged symmetrically. The sealing rings 3 do not contact the cathode catalyst layer 5-1 and the anode catalyst layer 5-2.

[0043] Of the two sealing rings mentioned above:

[0044] One side of the sealing ring contacts the position of the N117 proton exchange membrane that is not coated with the anode catalyst layer, and the other side contacts the corresponding bipolar plate 2 with flow channels; the sealing ring 3 does not contact the anode catalyst layer.

[0045] The other sealing ring has one side in contact with the position of the N117 proton exchange membrane that is not coated with the cathode catalyst layer, and the other side in contact with the corresponding bipolar plate 2 with flow channels; the sealing ring 3 does not contact the cathode catalyst layer.

[0046] In this invention, the porosity of the cathode gas diffusion layer 4-1 is gradient-distributed; the porosity of the carbonaceous diffusion layer near the oxide-derived silver (OD-Ag) / carbon nanotube (CNT) catalyst layer is 65-78%, preferably 74-76%, such as 75%, and the porosity of the side away from the oxide-derived silver (OD-Ag) / carbon nanotube (CNT) catalyst layer is 50-60%, preferably 54-56%, such as 55%.

[0047] Preferably, the device employs a zero-gap membrane electrode assembly (MEA) structure.

[0048] In industrial applications, the cathode gas diffusion layer 4-1 is a carbonaceous diffusion layer with a thickness of 200-300 μm, preferably 240-260 μm, including 250 μm. Carbon paper is preferred as the carbonaceous diffusion layer.

[0049] A gradient porosity structure is formed by laser etching of the carbonaceous diffusion layer. This structure can maintain the smooth flow of CO2 gas while forming a stable three-phase interface (gas-liquid-solid), promoting CO2 adsorption and proton transport to the catalytic site, and adapting to the conductivity characteristics of the modified N117 proton exchange membrane.

[0050] In this invention, the anode gas diffusion layer is made of titanium felt with a porosity of about 60% (e.g., 58-62%) and a thickness of 200-500 μm. It has good conductivity, corrosion resistance and gas diffusion performance, and can quickly transport protons generated by the anode to the N117 membrane, while timely desorbing oxygen generated by the anode to prevent oxygen from diffusing across the membrane to the cathode.

[0051] The modified N117 proton exchange membrane used in this invention has a tensile strength ≥25MPa and exhibits no significant swelling or degradation at an operating temperature of 80-90℃. Compared to thin proton exchange membranes, its CO2 transmembrane diffusion rate is reduced by more than 30%, and its resistance to anodic oxidation is improved by more than 50%, enabling long-term stable operation in industrial applications.

[0052] The device of this invention uses a 175μm thick modified N117 proton exchange membrane as the core for proton conduction and anode-cathode separation. Through the structural adaptation of the electrodes and the membrane, it achieves efficient CO2 reduction to CO. The specific working principle is as follows:

[0053] An external power source provides DC voltage, and electrons flow from the anode to the cathode through the external circuit.

[0054] The oxygen evolution reaction (OER) occurs at the anode: 2H₂O → O₂↑ + 4H₂O + + 4e - The generated H + Driven by the concentration gradient, the sulfonic acid groups of the modified N117 proton exchange membrane are rapidly transported to the cathode. The 175μm thickness of the modified N117 proton exchange membrane ensures proton conduction while effectively blocking CO2 diffusion to the anode and oxygen diffusion to the cathode.

[0055] The carbon dioxide reduction reaction (CO2RR) occurs at the cathode: CO2 + 2H+ + + 2e - → CO↑ + H2O, under the highly selective catalytic action of OD-Ag / CNT catalyst, CO2 is efficiently reduced to CO. The gradient porosity gas diffusion layer provides a stable three-phase interface for the reaction, promoting CO2 adsorption, proton binding and CO product desorption.

[0056] The CO gas generated at the cathode is separated and collected by a gas-liquid separator. Unreacted CO2 is recycled back into the cathode channel through a circulation system. The CO2 recycling rate is ≥95%. The low CO2 permeability of the N117 membrane significantly reduces CO2 transmembrane loss.

[0057] Beneficial effects

[0058] This invention uses a 175μm modified N117 proton exchange membrane as its core, designs a membrane electrode assembly, and applies the assembly to a PEM electrolyzer CO2RR CO production device. Through precise adaptation of the membrane, electrodes, and process, the contradiction between thick-film proton conduction and thin-film stability is resolved. Its advantages include:

[0059] 1. Precise selection of core membrane materials: A modified N117 proton exchange membrane with a thickness of 175μm is selected. Compared with thin membranes, its mechanical strength, gas barrier properties and degradation resistance are significantly improved, CO2 permeability is reduced by more than 30%, and the resistance to anodic oxidation is increased by more than 50%, achieving long-term stable operation at the industrial level. At the same time, through optimization of the catalyst layer structure, the shortcomings of thick membranes in proton conduction and voltage loss are made up for.

[0060] 2. Catalyst and membrane adaptation design: The high-activity OD-Ag / CNT cathode catalyst has a high surface defect density, strong CO2 adsorption and reduction capacity, and hydrogen evolution side reaction efficiency as low as 10%. It can reduce reaction overpotential, offset the slight voltage loss caused by the modified N117 thick film, and ensure the energy efficiency of the device.

[0061] 3. Gas diffusion layer structure adapted to thick film: The cathode gradient porosity gas diffusion layer design optimizes CO2 mass transfer and proton transport paths, and is adapted to the proton conduction characteristics of the modified N117 film, ensuring the stability of the three-phase interface and improving reaction efficiency.

[0062] 4. Process parameters adapted to the modified N117 membrane: The MEA hot pressing parameters (140℃, 7.0 MPa, 5min) and the start-up, shutdown and operation parameters of the device were optimized to ensure that the modified N117 membrane is fully wetted and activated, and the contact resistance between the membrane and the electrode interface is low. At the same time, the membrane is wetted and pressure-held for protection during the shutdown phase, which extends the service life of the membrane.

[0063] 5. Strong industrial adaptability: The CO2 recycling rate of the device is ≥95%, and the purity of CO products can reach ≥99.9%; the modified N117 membrane has excellent stability, which can ensure the device can operate continuously and stably for more than 1000 hours, with low maintenance costs. It can be directly coupled with the CO2 emission system of industries such as coal chemical and steel, and is also compatible with renewable energy sources such as photovoltaic and wind power to achieve green electricity to green carbon. Attached Figure Description

[0064] Figure 1 This is a schematic diagram of the membrane electrode assembly used in an embodiment of the present invention.

[0065] Figure 2 This is a microscopic morphology image of the OD-Ag / CNT prepared in Example 1 of the present invention.

[0066] Figure 3 This is a photograph of the membrane electrode assembly used in Example 1.

[0067] Figure 4 This is a schematic diagram of the structure of the MEA after it has been assembled into a PEM electrolyzer.

[0068] Figure 5 This is a schematic diagram of the cathode bipolar plate and the anode bipolar plate.

[0069] Figure 6 This is the LSV diagram of the membrane electrode obtained in Embodiment 1 of the present invention.

[0070] Figure 7 The figure shows the stability test results of the membrane electrode obtained in Example 1 of the present invention after it is assembled into a PEM electrolyzer.

[0071] from Figure 1 The basic structure of the membrane electrode assembly designed in this invention can be seen from the diagram. Figure 1 In the diagram, 5-1 is the cathode catalytic layer, 5-2 is the anode catalytic layer, and 6 is the N117 proton exchange membrane.

[0072] from Figure 2 It can be seen that the size of OD-Ag is less than or equal to 100 nm, and the carbon nanotubes are evenly distributed.

[0073] from Figure 3 The catalyst can be found to be attached to the modified N117 proton exchange membrane, and the coverage area of ​​the catalyst is smaller than the area of ​​the modified N117 proton exchange membrane.

[0074] Figure 4 In the diagram, 1 is the end plate, 2 is the bipolar plate with flow channels, 3 is the sealing ring, 4-1 is the cathode gas diffusion layer, 4-2 is the anode gas diffusion layer, 5-1 is the cathode catalyst layer, 5-2 is the anode catalyst layer, and 6 is the N117 proton exchange membrane; the basic structure of the PEM electrolyzer can be seen from the figure.

[0075] Figure 5 In the diagram, 2-1 is a schematic diagram of the cathode bipolar plate, and 2-2 is a schematic diagram of the anode bipolar plate. Figure 5 The basic structure and function of the cathode and anode bipolar plates can be seen from this.

[0076] from Figure 6 The results show the relationship between the changes in tank voltage and current density of the membrane electrode obtained in Example 1 during testing.

[0077] from Figure 7 As can be seen from the results, the membrane electrode exhibits excellent stability after 1000 hours of testing. Detailed Implementation

[0078] Example 1

[0079] MEA Preparation: This embodiment optimizes the hot-pressing and coating parameters of the MEA to ensure a tight fit between the membrane and the electrode, avoiding excessive interfacial contact resistance, based on the 175μm thickness characteristics of the N117 proton exchange membrane. The specific steps are as follows:

[0080] Preparation of the cathode catalyst OD-Ag / CNT: The method for preparing the oxide-derived silver (OD-Ag) / CNT catalyst of the present invention is as follows. This catalyst is compatible with the N117 film and can effectively offset the voltage loss caused by the thick film, thereby improving CO selectivity.

[0081] Precursor preparation: Dissolve 1g AgNO3 in 50mL deionized water according to the ratio, add 0.5g CNT; sonicate for 30min, add 2mol / L NaOH solution to adjust pH to 10, stir for 2h to obtain Ag2O / CNT precursor;

[0082] Electrochemical reduction: The precursor was coated on carbon paper as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. The catalyst was reduced in 1 M KHCO3 solution at a constant potential of -0.2 V (vs. RHE) for 60 min to obtain a porous OD-Ag / CNT catalyst.

[0083] Post-treatment: After peeling the catalyst off the carbon paper, wash it with deionized water until neutral, and dry it under vacuum at 60°C for 12 hours for later use.

[0084] The OD-Ag catalyst prepared by this method has abundant active sites, which can significantly improve CO2 adsorption capacity and CO selectivity, reduce the efficiency of hydrogen evolution side reaction to below 10%, and when used in combination with modified N117 proton exchange membrane, it can maintain a low overpotential at a current density of 1000 mA / cm², ensuring the energy efficiency of the device.

[0085] N117 proton exchange membrane modification: N117 proton exchange membrane (thickness 175μm) was boiled in 5% H2O2, 0.5mol / L H2SO4 and deionized water for 1h each, cooled to room temperature and drained, keeping the membrane wet; the modified N117 proton exchange membrane was obtained.

[0086] Preparation of cathode catalyst ink: 0.24 g of OD-Ag / CNT catalyst, 105 μL of Nafion solution (20 wt%) and 67.8 mL of mixed solvent (mass ratio, ethanol:water = 1.76:1) were mixed and ultrasonically dispersed for 60 min to form a uniform catalyst ink with a solid content of 0.4 wt%.

[0087] Cathode catalyst layer coating: The catalyst ink was coated on one side of the modified N117 proton exchange membrane using ultrasonic spraying. The spraying temperature was 80℃ and the loading was precisely controlled at 0.9mg / cm². A modified N117 proton exchange membrane with a cathode catalyst layer was obtained.

[0088] Preparation of anode catalyst ink: 0.21 g IrO2 catalyst, 80 μL Nafion solution and 10 mL mixed solvent (mass ratio, ethanol:water = 1.76:1) were mixed according to the ratio and ultrasonically dispersed for 60 min to form a uniform catalyst ink with a solid content of 0.35 wt%.

[0089] Anode catalyst layer coating: Catalyst ink was coated onto the other side of the modified N117 proton exchange membrane with a cathode catalyst layer using ultrasonic spraying. The spraying temperature was 80℃ and the loading was 1.0 mg / cm². A modified N117 proton exchange membrane with a cathode catalyst on one side and an anode catalyst on the other side was obtained.

[0090] MEA hot pressing: A modified N117 proton exchange membrane with a cathode catalyst on one side and an anode catalyst on the other side is hot pressed to obtain a MEA; the hot pressing temperature is 140℃, the pressure is 7.0MPa, and the time is 5min; the effective area of ​​the obtained MEA is 25 cm² (i.e., the coating area of ​​the cathode catalyst and also the coating area of ​​the anode catalyst), and the contact resistance between the membrane and the electrode interface is ≤5 mΩ·cm².

[0091] Device performance testing

[0092] Using the MEA prepared in Example 1, according to Figure 4 The membrane was assembled into a PEM electrolyzer (effective working area 25 cm²) and subjected to performance and stability tests to verify the compatibility between the membrane and the device.

[0093] The PEM electrolyzer includes two end plates 1, two bipolar plates with flow channels 2, two sealing rings 3, a cathode gas diffusion layer 4-1, an anode gas diffusion layer 4-2, a cathode catalyst layer 5-1, an anode catalyst layer 5-2, and an N117 proton exchange membrane 6. The cathode catalyst layer 5-1 and the anode catalyst layer 5-2 are located on opposite sides of the modified N117 proton exchange membrane 6 and are attached to it. The cathode gas diffusion layer 4-1 is in contact with the cathode catalyst layer 5-1, and the anode gas diffusion layer 4-2 is in contact with the anode catalyst layer 5-2. One of the two sealing rings 3 is located on one side of the cathode gas diffusion layer 4-1, and the other sealing ring 3 is located on one side of the anode gas diffusion layer 4-2.

[0094] Two bipolar plates 2 with flow channels are respectively arranged on one side of two sealing rings 3, and two end plates 1 are respectively arranged on one side of two bipolar plates 2 with flow channels;

[0095] With the modified N117 proton exchange membrane 6 as the axis of symmetry, the two end plates 1, the two bipolar plates 2 with flow channels, and the two sealing rings 3 are arranged symmetrically. The sealing rings 3 do not contact the cathode catalyst layer 5-1 and the anode catalyst layer 5-2.

[0096] Of the two sealing rings mentioned above:

[0097] One side of the sealing ring contacts the N117 proton exchange membrane that is not coated with the anode catalyst layer, and the other side contacts the corresponding bipolar plate 2 with flow channels; the sealing ring 3 does not contact the anode catalyst layer.

[0098] The other sealing ring has one side in contact with the position of the N117 proton exchange membrane that is not coated with the cathode catalyst layer, and the other side in contact with the corresponding bipolar plate 2 with flow channels; the sealing ring 3 does not contact the cathode catalyst layer.

[0099] The porosity of the cathode gas diffusion layer 4-1 exhibits a gradient distribution; the porosity of the carbonaceous diffusion layer is 75% on the side closer to the oxide-derived silver (OD-Ag) / carbon nanotube (CNT) catalyst layer and 55% on the side farther from the oxide-derived silver (OD-Ag) / carbon nanotube (CNT) catalyst layer.

[0100] The cathode gas diffusion layer 4-1 is carbon paper with a thickness of 250 μm; the gradient porosity structure is formed on the carbon paper by laser etching.

[0101] The anode gas diffusion layer is made of titanium felt with a porosity of about 60% and a thickness of 250 μm.

[0102] The specific test results are as follows:

[0103] Test conditions: CO2 flow rate 400 sccm, deionized water flow rate 200 mL / min, cathode temperature 60 ℃, anode temperature 60 ℃, humidity 85% RH, modified N117 proton exchange membrane fully wetted and activated;

[0104] The test results are as follows: at a current density of 1000 mA / cm², the battery voltage is 2.21 V, the CO Faradaic efficiency is 90.2%, and the hydrogen evolution efficiency is only 9.8%; stability test: after continuous operation for 1000 hours, the CO Faradaic efficiency remains above 88.5%, the current density decay rate is ≤0.01% / h, the N117 membrane shows no obvious swelling, degradation, or pinhole phenomena, the proton conductivity remains above 0.08 S / cm, and the CO2 permeability does not increase significantly;

[0105] Individual performance test of N117 membrane: After the test, the electrolytic cell was disassembled. The tensile strength of the N117 membrane was still ≥23MPa, the degree of sulfonation did not decrease significantly, and there was no catalyst particle deposition on the membrane surface, which proves that it has excellent anti-fouling and anti-degradation capabilities.

[0106] Example 2

[0107] This embodiment is based on Example 1, only adjusting the cathode catalyst loading. The remaining steps (catalyst preparation, anode catalyst coating, membrane pretreatment, hot pressing parameters, etc.) are completely consistent with Example 1. The specific difference is that the loading is adjusted to 0.8 mg / cm² when coating the cathode catalyst layer.

[0108] The test conditions were exactly the same as in Example 1, and the specific test results are as follows:

[0109] At a current density of 1000 mA / cm², the battery voltage is 2.27 V, the CO Faradaic efficiency is 88.6%, and the hydrogen evolution efficiency is 11.4%. Stability testing shows that after 1000 hours of continuous operation, the CO Faradaic efficiency remains above 86.3%, the current density decay rate is ≤0.012% / h, the N117 membrane shows no obvious swelling, degradation, or pinholes, the proton conductivity remains above 0.078 S / cm, and the CO2 permeability shows no significant increase.

[0110] Individual performance test of N117 membrane: After the test, the electrolytic cell was disassembled. The tensile strength of the N117 membrane was still ≥22.8MPa, the degree of sulfonation did not decrease significantly, there was no catalyst particle deposition on the membrane surface, the compatibility was good, and the performance was slightly inferior to that of Example 1.

[0111] Example 3

[0112] This embodiment is based on embodiment 1, only the MEA hot pressing parameters are adjusted, and the rest of the steps are completely the same as in embodiment 1. The specific difference is that the MEA hot pressing molding parameters are adjusted to be hot pressed for 6 minutes at 135℃ and 7.0MPa.

[0113] The test conditions were exactly the same as in Example 1, and the specific test results are as follows:

[0114] At a current density of 1000 mA / cm², the battery voltage is 2.29 V, the CO Faradaic efficiency is 88.1%, and the hydrogen evolution efficiency is 11.9%. Stability testing showed that after 1000 hours of continuous operation, the CO Faradaic efficiency remained above 85.8%, the current density decay rate was ≤0.013% / h, the N117 membrane showed no significant swelling, degradation, or pinholes, the proton conductivity remained above 0.077 S / cm, and the CO2 permeability showed no significant increase.

[0115] Individual performance test of N117 membrane: After the test, the electrolytic cell was disassembled. The tensile strength of N117 membrane was still ≥22.7MPa, the degree of sulfonation did not decrease significantly, there was no catalyst particle deposition on the membrane surface, and the contact resistance between the membrane and the electrode interface was ≤6.2 mΩ·cm². The compatibility was good, but the performance was slightly inferior to that of Example 1.

[0116] Example 4

[0117] This embodiment is based on Example 1, only adjusting the solid content of the catalyst ink. The remaining steps are completely the same as in Example 1. The specific difference is that the solid content of the cathode catalyst ink is adjusted to 0.38wt%, and the solid content of the anode catalyst ink is adjusted to 0.32wt%.

[0118] The test conditions were exactly the same as in Example 1, and the specific test results are as follows:

[0119] At a current density of 1000 mA / cm², the battery voltage is 2.25 V, the CO Faradaic efficiency is 88.9%, and the hydrogen evolution efficiency is 11.1%. Stability testing showed that after 1000 hours of continuous operation, the CO Faradaic efficiency remained above 86.7%, the current density decay rate was ≤0.011% / h, the N117 membrane showed no significant swelling, degradation, or pinholes, the proton conductivity remained above 0.079 S / cm, and the CO2 permeability showed no significant increase.

[0120] Individual performance test of N117 membrane: After the test, the electrolytic cell was disassembled. The tensile strength of the N117 membrane was still ≥22.9MPa, the degree of sulfonation did not decrease significantly, there was no catalyst particle deposition on the membrane surface, the compatibility was good, and the performance was slightly inferior to that of Example 1.

[0121] Comparative Example 1

[0122] The other conditions were the same as in Example 1, except that CNTs were not used in the preparation of the cathode catalyst.

[0123] After assembling the obtained MEA into a 25 cm² PEM electrolyzer, the cell voltage was 2.58 V at a current density of 1000 mA / cm², the CO Faradaic efficiency was 75.3%, and the hydrogen evolution efficiency was 24.7%. Stability test: After 1000 hours of continuous operation, the CO Faradaic efficiency was only 70.1%, and the current density decay rate was 0.035% / h.

[0124] Comparative Example 2

[0125] Other conditions were the same as in Example 1, except that: when preparing the cathode catalyst, 1g of AgNO3 was dissolved in 50mL of deionized water, 0.5g of CNT was added and ultrasonically dispersed for 30min, 2mol / L NaOH solution was added dropwise to adjust the pH to 10, and the reaction was stirred for 2h to obtain the Ag2O / CNT precursor;

[0126] The precursor was coated onto a carbonaceous diffusion layer and then reduced under a hydrogen atmosphere to obtain an Ag / carbon nanotube (CNT) catalyst.

[0127] After assembling the obtained MEA into a 25 cm² PEM electrolyzer, the cell voltage was 2.42 V at a current density of 1000 mA / cm², the CO Faradaic efficiency was 81.5%, and the hydrogen evolution efficiency was 18.5%. Stability test: After 1000 hours of continuous operation, the CO Faradaic efficiency was only 78.3%, and the current density decay rate was 0.022% / h.

[0128] Comparative Example 3

[0129] The other conditions are the same as in Example 1, except that IrO2 is replaced with an equal amount of Pt.

[0130] After assembling the obtained MEA into a 25 cm² PEM electrolyzer, the cell voltage was 2.67 V at a current density of 1000 mA / cm², the CO Faradaic efficiency was 72.8%, and the hydrogen evolution efficiency was 27.2%. Stability test: After 1000 hours of continuous operation, the CO Faradaic efficiency was only above 68.4%, and the current density decay rate was 0.042% / h.

[0131] Comparative Example 4

[0132] The other conditions are the same as in Example 1, except that the N117 membrane is treated with only water.

[0133] After assembling the obtained MEA into a 25 cm² PEM electrolyzer, the cell voltage was 2.35 V at a current density of 1000 mA / cm², the CO Faradaic efficiency was 83.7%, and the hydrogen evolution efficiency was 16.3%. Stability test: After 1000 hours of continuous operation, the CO Faradaic efficiency was only above 80.5%, and the current density decay rate was 0.018% / h.

Claims

1. A method of using an electrochemical carbon dioxide reduction device, characterized in that: This includes assembling an electrochemical carbon dioxide reduction device into a PEM electrolyzer to form a CO2RR CO production device; The device includes a membrane electrode assembly, which consists of a cathode catalyst layer (5-1), an anode catalyst layer (5-2), and an N117 proton exchange membrane (6). The cathode catalyst layer (5-1) and the anode catalyst layer (5-2) are located on both sides of the N117 proton exchange membrane (6) and are attached to the N117 proton exchange membrane (6). The cathode catalyst layer (5-1) is made of OD-Ag / CNT catalyst, and the anode catalyst layer (5-2) is made of IrO2 catalyst. The OD-Ag / CNT catalyst used was prepared according to the following scheme: Prepare AgNO3 and CNT by mass ratio of AgNO3:CNT = 1:0.4~0.6, then dissolve the prepared AgNO3 in deionized water, add the prepared carbon nanotubes to it, and after ultrasonic dispersion, adjust the pH of the solution system to 9.8~10.2, stir the reaction for at least 1 hour to obtain Ag2O / CNT precursor; An Ag₂O / CNT precursor was coated onto a carbonaceous current collector as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. The reaction was carried out in a 0.4–0.6 mol / L H₂SO₄ solution at a constant potential of -0.18–-0.22 V for at least 30 min to obtain an OD-Ag / CNT catalyst with a current collector; the voltage is relative to the RHE. The catalyst was then stripped from the carbonaceous current collector, washed with deionized water until neutral, and finally dried under vacuum to obtain the OD-Ag / CNT catalyst. The electrochemical carbon dioxide reduction device is prepared by the following steps: Step 1: First, place a 175μm thick N117 proton exchange membrane in a solution of 5% H2O2 and 0.5mol / L H2SO4, heat it to 95~105℃, and keep it at that temperature for at least 30min to obtain a pre-modified N117 proton exchange membrane. Then, place the pre-modified N117 proton exchange membrane in deionized water, heat it to 95~105℃, and keep it at that temperature for at least 30min to obtain a modified N117 proton exchange membrane. Step 2: Prepare 0.2-0.3 g of OD-Ag / CNT catalyst by mixing 90-150 μL of Nafion solution and 50-75 mL of mixed solvent. Mix the OD-Ag / CNT catalyst, Nafion solution, and mixed solvent thoroughly to obtain cathode catalyst ink. Then, spray the cathode catalyst ink onto one side of the modified N117 proton exchange membrane to obtain a modified N117 proton exchange membrane with the cathode catalyst. The spraying temperature is 70-90℃, and the loading of OD-Ag / CNT catalyst on the modified N117 proton exchange membrane is 0.8-1.0 mg / cm³. 2 ; Step 3: Mix the IrO2 catalyst, Nafion solution, and mixed solvent evenly according to the ratio of 0.15~0.3g IrO2 catalyst, 60~100μL Nafion solution, and 10~20mL mixed solvent to obtain the anolyte catalyst ink; spray the anolyte catalyst ink onto the other side of the modified N117 proton exchange membrane; thus obtaining a modified N117 proton exchange membrane with a cathode catalyst on one side and an anolyte catalyst on the other side. The spraying temperature was 70~90℃, and the loading of the anolyte catalyst on the modified N117 proton exchange membrane, which had a cathode catalyst on one side and an anolyte catalyst on the other, was 0.8~1.2 mg / cm³. 2 ; Step 4: Under the conditions of temperature of 120~160℃ and pressure of 3~8MPa, the modified N117 proton exchange membrane with a cathode catalyst on one side and an anode catalyst on the other side is hot-pressed to obtain MEA. The contact resistance between the membrane and the catalyst layer is ≤5mΩ・cm². The PEM electrolyzer includes two end plates (1), two bipolar plates with flow channels (2), two sealing rings (3), a cathode gas diffusion layer (4-1), an anode gas diffusion layer (4-2), a cathode catalyst layer (5-1), an anode catalyst layer (5-2), and an N117 proton exchange membrane (6). The cathode catalyst layer (5-1) and the anode catalyst layer (5-2) are located on both sides of the modified N117 proton exchange membrane (6) and are attached to the modified N117 proton exchange membrane (6). The cathode gas diffusion layer (4-1) is in contact with the cathode catalyst layer (5-1), and the anode gas diffusion layer (4-2) is in contact with the anode catalyst layer (5-2). One of the two sealing rings (3) is arranged on one side of the cathode gas diffusion layer (4-1), and the other of the two sealing rings (3) is arranged on one side of the anode gas diffusion layer (4-2). Two bipolar plates (2) with flow channels are respectively arranged on one side of two sealing rings (3), and two end plates (1) are respectively arranged on one side of two bipolar plates (2) with flow channels; With the modified N117 proton exchange membrane (6) as the axis of symmetry, two end plates (1), two bipolar plates with flow channels (2), and two sealing rings (3) are arranged symmetrically. The porosity of the cathode gas diffusion layer (4-1) exhibits a gradient distribution; the porosity of the carbonaceous diffusion layer is 65-78% on the side closer to the OD-Ag / CNT catalyst layer and 50-60% on the side farther from the OD-Ag / CNT catalyst layer. The cathode gas diffusion layer (4-1) is a carbonaceous diffusion layer with a thickness of 200~300μm; The anode gas diffusion layer is made of titanium felt with a porosity of 58-62% and a thickness of 200-500 μm.

2. The method of using the electrochemical carbon dioxide reduction device according to claim 1, characterized in that: OD-Ag / CNT catalysts were prepared by electrochemical reduction of Ag₂O precursor. The OD-Ag particle size was 10–100 nm, and the surface defect density was 1.2–1.6 × 10⁻⁶. 18 Units / m² 3. The method of using the electrochemical carbon dioxide reduction device according to claim 1, characterized in that: In step two, 0.24 g of OD-Ag / CNT catalyst, 105 μL of Nafion solution, and 67.8 mL of mixed solvent were mixed in the specified proportions and ultrasonically dispersed for 60 min. Then, the catalyst ink was coated onto the modified N117 proton exchange membrane using an ultrasonic spraying method at 80℃. The loading of OD-Ag / CNT catalyst on the modified N117 proton exchange membrane was 0.9 mg / cm³. 2 The mixed solvent is composed of ethanol and water in a mass ratio of 1.76:1; the concentration of solute in the Nafion solution is 20 wt%.

4. The method of using the electrochemical carbon dioxide reduction device according to claim 3, characterized in that: In step three, 0.21g of IrO2 catalyst, 80 μL of Nafion solution and 10mL of mixed solvent are mixed in proportion and ultrasonically dispersed for 60min to obtain anode catalyst ink; the mixed solvent is composed of ethanol and water in a mass ratio of ethanol:water = 1.76:

1. The anolyte catalyst ink was sprayed onto the other side of the modified N117 proton exchange membrane, resulting in a modified N117 proton exchange membrane with a cathode catalyst on one side and an anolyte catalyst on the other side. The spraying temperature was 80℃, and the loading of the anolyte catalyst on the modified N117 proton exchange membrane with a cathode catalyst on one side and an anolyte catalyst on the other side was 1.0 mg / cm³. 2 .

Citation Information

Patent Citations

  • Flue gas waste heat in-situ utilization and carbon dioxide advanced treatment coupling system

    CN116293761A

  • MEA electrolytic bath device and method for electrocatalytic carbon dioxide reduction

    CN120844112A

  • Preparation process of composite hydrogen type proton exchaning membrane for fuel cell

    CN1861667A

  • Co2-reduction membrane electrode assembly including cation exchange membrane, co2-reduction assembly including same MEA, and method of manufacturing same mea

    US20240093388A1